Penggunaan ubi kayu putih sebagai media alternatif kultur Candida albicans - Safridha Kemala Putri; Syarifah Wahyuni; Farah Fajarna (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Candida albicans is a fungus that requires organic compounds as a source of carbon and energy for growth and metabolic processes obtained from carbohydrates. One of the alternative media from materials that are readily available in nature but have not been widely utilized, namely from tubers such as white cassava (Manihot esculenta C.), which is believed to have a high carbohydrate content according to the needs of Candida albicans.Objectives: The study aims to determine whether white cassava can be used as an alternative medium for Candida albicans culture.Methods: The method used in this study is experimental, namely by seeing whether Candida albicans can grow or not on alternative media of white cassava. This study begins with the collection of Candida albicans specimens in patients with candidiasis, and then research is carried out at the Microbiology Laboratory of the Medical Laboratory Technology Department of the Aceh Ministry of Health Polytechnic. This research was carried out in 2020. The sample of this study was white cassava meat, as much as 150 grams. This study collected data by culturing Candida albicans on alternative media with raw materials for white cassava meat. For the identification of Candida albicans species, confirmation tests were carried out using the Germ tube test method. Furthermore, the data obtained from the assessment of colony growth (+) positive Candida albicans on white cassava media (Manihot esculenta C.) incubated for 72 hours (± three days) at 370C.Results: Based on the macroscopic and microscopic assessments, Candida albicans can grow well on white cassava media (Manihot esculenta C.).Conclusion: Alternative media of white cassava raw materials (Manihot esculenta C.) can be used as a culture medium for Candida albicans.